Story, dialogue and caring about what matters to people: progress towards evidence-enriched policy and practice. (1st November 2020) - Andrews, Nick; Gabbay, John; Le-May, Andreé; Miller, Emma; Petch, Alison; O'Neill, Martin
Abstract : Background: Evidence-based practice in social care and health is widely promoted. Making it a reality remains challenging, partly because practitioners generally see practice-based knowledge as more relevant than empirical research. A further challenge regarding the creative, contextual use of research and other evidence including lived experience and practice-based knowledge is that practitioners, especially in frontline care services, are often seen not as innovators, but recipients of rules and guidelines or followers of pre-determined plans. Likewise, older people are not generally recognised as co-creators of knowledge, learning and development but as passive recipients of care, or objects of research.Aims: This study aimed to address the above issues, through a collaborative and appreciative endeavour involving researchers; social care and health practitioners; managers; older people and carers in 6 sites across Wales and Scotland.Methods: We used participatory action research methodology, applying a dialogic storytelling approach, which enabled participants to explore and address 7 already published research-based 'Challenges' regarding what matters most to older people with high-support needs.Findings: Participants discovered and addressed five elements required in developing evidence-enriched practice; the creation of supportive and relationship-centred research and practice environments; the valuing of diverse types of evidence; the use of engaging narratives to capture and share evidence; the use of dialogue-based approaches to learning and development; and the recognition and resolution of systemic barriers to development.Discussion and conclusion: Although existing literature covers each element, this project was novel in collectively exploring and addressing all five elements together, and in its use of multiple forms of story, which engaged hearts and minds, positive outcomes were achieved.